Indicaciones de estudio urodinámico - Valdevenito S., Juan Pablo; Kobus G., Cristóbal; Muñoz H., Sebastián; Bull C., Leonardo (Revista Hospital Clínico Universidad de Chile, 2019)
The basic objective of urodynamics is to reproduce the patient’s symptoms while evaluatingthe lower urinary tract directly, with objective quantification of parameters, correlating thesymptoms with the findings of the test. Traditionally, it is used: a) to diagnose lower urinarytract dysfunction, quantify its severity and determine the most significant abnormality, b) topredict the consequences of lower urinary tract dysfunction on the upper urinary tract, c) topredict the results of therapeutic interventions and possible complications and d) to investigatethe causes of treatment failures. In this article we will refer to the indications of urodynamicstaking into account the recommendations of the main international urological societies: 1) inwomen with urinary incontinence, with emphasis on those who have stress urinary incontinenceand who will undergo surgery, 2) in men with non-neurogenic lower urinary tract symptomssuggestive of benign prostatic hyperplasia, and 3) in patients with neurologic involvement ofthe lower urinary tract (“neurogenic bladder”), considering the classification of neurologicaldisorders according to the risk over the upper urinary tract.